2018
DOI: 10.1186/s12884-018-2007-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing decision-making for caesarean section in Sweden – a qualitative study

Abstract: BackgroundRising rates of caesarean section (CS) are a concern in many countries, yet Sweden has managed to maintain low CS rates. Exploring the multifactorial and complex reasons behind the rising trend in CS has become an important goal for health professionals. The aim of the study was to explore Swedish obstetricians’ and midwives’ perceptions of the factors influencing decision-making for CS in nulliparous women in Sweden.MethodsA qualitative design was chosen to gain in-depth understanding of the factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 33 publications
(30 reference statements)
3
36
3
1
Order By: Relevance
“…In general, obstetricians are seen as more likely than midwives to agree to a women's request for CS . A recent study, interviewing 11 midwives and five obstetricians in Sweden, where the CS rate is only 17%, found that women were very involved in decision‐making for most aspects of care, including CS on request in very rare situations . The midwives described how women who were fearful of birth were cared for:
“We have Aurora, counselling team with midwives.
…”
Section: Sdm In Maternity Carementioning
confidence: 99%
See 4 more Smart Citations
“…In general, obstetricians are seen as more likely than midwives to agree to a women's request for CS . A recent study, interviewing 11 midwives and five obstetricians in Sweden, where the CS rate is only 17%, found that women were very involved in decision‐making for most aspects of care, including CS on request in very rare situations . The midwives described how women who were fearful of birth were cared for:
“We have Aurora, counselling team with midwives.
…”
Section: Sdm In Maternity Carementioning
confidence: 99%
“…[A] woman who wish for a CS comes to this counselling programme and talks to a midwife, so we give them options like induction, pain relief, birth plan and … a CS contract. Which means when… in labour [if] the woman feels that it's too traumatic or too painful… she can by herself request for CS… And when they have this contract they feel … in control…” (FGI with Midwives, Site 1).” (p4)…”
Section: Sdm In Maternity Carementioning
confidence: 99%
See 3 more Smart Citations